Changing Assessment - Hughes, Conrad (Brill, 2025)
Since the Delors report, education reformers have been working to create curricula that allow human beings to flourish. Schools should not only be places where we learn to be and learn to live together, but also places where the way we assess students valorises the diverse range of human gifts within them. Yet, most schools remain locked in a 19th-century assessment structure that prevents young people from exploring the full variety and extent of their talents, forcing them to perform on a narrow, high-stakes track. When will this change?